PENGARUH SHARING ECONOMY, SISTEM BAGI HASIL, DAN FLEXTIME TERHADAP INTENSI PENGEMUDI GO-JEK JAKARTA PUSAT DENGAN EFEKTIVITAS SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pengemudi Go-jek Jakarta Pusat) - Andiani Ken Astri Amanda; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2018)
Nowadays, motorcycle taxi transformed into a professional motorcycle taxi with technological sophistication by the existence of Go-JekAlthough it is known that Go-Jek's technology app has had a positive impact, it has problems. First, the presence of Go-jek denied by the motorcycle taxi.Secondly, the operates regulation of Go-jek. The criticisms that go to Go-jek are the problem of motorcycle taxi (motorcycle). The purpose of this study is to determine the effect of sharing economy, profit sharing system, and flextime to intention drivers gojek area of central jakarta with effectiveness as intervening variable. This type of research is explorative research. The sampling technique used purposive sampling method. The number of samples taken as many as 100 respondents. Data were analyzed through validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, t test, F test, and sobel test with the help of SPSS program. Based on the results of descriptive analysis, showing the results of the study economy economy is in good category of 37.5 percent. Variable profit sharing system is in good category, amounting to 37.8 percent. Flexible variable is in good category, 38,6%, effectiveness variable is in high category, equal to 39,7% and intention variable in high category equal to 39,1%. Suggestions in this study is about other ojek online should uses the concept of business sharing economy in order to facilitate the registration requirements for public intention to become higher.